Pengembangan Media Pembelajaran Berbasis Website Materi Renang Gaya Crawl Dan Gaya Dada Untuk Peserta Didik - Redi Dana Yasa, Ketut; I Gede Suwiwa; I Komang Sukarata Adnyana (Universitas Pendidikan Ganesha, 2025)
This study aims to develop website-based learning media on breaststroke and freestyle swimming materials for grade VIII students of SMP Negeri 6 Singaraja. The type of research used in the study is the type of ADDIE model development research consisting of five stages, namely analysis, design, development, implementation, and evaluation. The development product was validated by content/learning material experts, learning design experts, and learning media experts. The subjects in this study were all grade VIII students of SMP Negeri 6 Singaraja. Data were collected using a questionnaire with the instrument used, namely a scale of 5 and the data analysis technique used was quantitative descriptive analysis. Based on the research results, the results of the material/teaching material expert test percentage of 90% qualified very well with input to sharpen the material, the learning design expert test obtained a percentage of 95% qualified very well with suggestions on the material components need to be strengthened with images and material management needs to be improved, solid material can be broken down into several pages, the learning media expert test obtained a percentage of 97% qualified very well with the presentation of titles, covers, dashboards and learning instructions, the small group test obtained a percentage of 85.4% qualified well, and the large group test obtained a percentage of 91.91% qualified well with input that the media can attract students' enthusiasm for learning, and the product practicality test obtained a percentage of 89.48% with a very practical category. Based on the research results, website-based learning media on breaststroke and freestyle swimming materials for class VIII students of SMP Negeri 6 Singaraja is very suitable for use by Junior High School (SMP) students as a learning resource, so that it can improve learning achievement and learning quality.